EFISIENSI USAHATANI CINCAU (Mesona palustris BL) DI KARANGTENGAH KABUPATEN WONOGIRI - SRI HUTAMI; SAMTO SAMTO (Universitas Sebelas Maret, 2008)
Cincau (plant the leaves of which used to produce a kind of gelatin) is one of plants that have usage to produce material for drinks, cosmetics, and antibiotics. This plant has been traditionally cultivated as commodity in Karangtengah sub-district for couple of decades.